Asuhan Nifas Menggunakan Terapi Non Farmakologi Terhadap Kecemasan Ibu Post Partum: Literature Review - Trisnawati, Yeni; Marbun, Lenny Marlina; Aulia, Devy Lestari Nurul; AnjanI, Arum Dwi (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Postpartum depression is a mood disorder that usually occurs between 2 to 6 weeks after childbirth. Symptoms include feeling depressed, a loss of interest, eating disorders, inability to sleep, physical fatigue, feelings of worthlessness, concentration difficulties, and suicidal thoughts. It is crucial to prevent the condition from worsening, with family and healthcare workers playing a key role in management. Non-pharmacological therapy offers an alternative for the prevention and treatment of postpartum depression. A review of journals from PubMed, Google Scholar, and Science Direct was conducted, focusing on publications from the last 5 to 10 years, with designs that are RCT or quasi-experimental. The respondents were postpartum mothers 20 postnatal mothers. A total of 15 primary studies were reviewed, revealing various preventive management strategies, including massage therapy, back massage, meridian acupoints massage, aromatherapy, facial touch (totok wajah), postnatal yoga, murrotal therapy from Al-Qur'an, body massage, exercise and wellness interventions, SMARTER therapy or Spiritual Management of Relaxation Therapy, Effleurage massage therapy, progressive muscle relaxation, Hypnobreastfeeding, Cognitive Behavioral Therapy (CBT). The management of non- pharmacological therapies has been scientifically proven to have a positive impact in preventing and reducing the incidence of depression postpartum. Keywords: Postpartum Depression, Non-Pharmacological, Alternative Therapy  ABSTRAK Depresi yang terjadi pada masa pasca melahirkan ini merupakan suatu gejala ketidaknormalan suasana hati, biasanya terjadi diantara 2-6 minggu pasca persalinan. Gejala seperti rasa tertekan, merasa kehilangan pada ketertarikan, terjadi gangguan pada pola makan, tidak dapat tidur, gejala lelah fisik, merasa seperti tidak berguna, gangguan konsentrasi dan bunuh diri. Perlu pencegahan keadaan yang lebih parah. Penanganan bersama keluarga dan Nakes. Terapi non-farmakologis menjadi alternatif pencegahan dan penanganan kejadian depresi ibu pascapartum. Penelaahan Jurnal di Pubmed, Google Scholar Sciece Direct dengan syarat waktu publikasi jurnal antara 5-10 tahun terakhir, desain RCT dan quasi eksperimental, responden ibu pascapartum depresi sedikitnya 20 ibu nifas. Studi primer yang diambil sebanyak 10 jurnal dan terdapat beberapa penatalaksanaan pencegahan depresi pada ibu pascapartum diantaranya adalah terapi Massage, Back massage, Meridian accupoints massage, Aromatherapy, Facial touch (totok Wajah), Yoga Postnatal, Terapi murrotal Al-Qur’an, Body massage, Exercise and wellness Interventions, Massage Terapi SMARTER atau Spiritual Management of Relaxation Therapy, massage terapi Effleurage, Progressive muscle relaxation, Hypnobreastfeeding, Cognitif Behavior Therapi (CBT). Penatalaksanaan terapi nofarmakologi tersebut terbukti secara ilmiah mempunyai dampak postif dalam mencegah serta mengurangi kejadian depresi pada ibu pascapartum. Kata Kunci: Kecemasan Pascapartum, Nonfarmakologi, Terapi Alternatif